Peran Guru Dalam Meningkatkan Rasa Percaya Diri Anak Usia Dini Di RA Al Hikmah Duri Kosambi Cengkareng - Nurasyifah; Desy Ayu Ningrum (Prodi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas PTIQ Jakarta, 2024)
Self-confidence is important for children, because a lack of confidence in their abilities will make children afraid and not confident to do something. feelings of doubt, anxiety, and lack of confidence that can interfere with various aspects of life. Someone who experiences this tends to have negative thoughts about themselves. Teachers play a very important role in helping the development of students to realize their life goals optimally. This study aims to analyze the role of teachers in increasing children's self-confidence in early childhood at RA Al Hikmah, West Jakarta. The methods used for data collection are observation, interviews and documentation. Data analysis with qualitative methods is presented with descriptive analysis methods. The results of the study indicate that teachers have an important role in increasing children's self-confidence, through the role of teachers as planners, observers, role models, facilitators, elabolators, evaluators. Children's self-confidence at RA Al Hikmah Duri Kosambi Cengkareng has increased such as never giving up daring to express opinions, daring to ask questions, prioritizing their own efforts from the help of others, and appearing calm.